Los silencios de niños hablantes de chinanteco en diversas situaciones escolares - Rebolledo Angulo, Valeria (2015)
This article analyzes, from an ethnographic perspective and a sociocultural framework, the construction of silences in the interaction between students and teachers in a multilingual classroom situation in an indigenous community in méxico. the analysis reveals how the silence of the chinanteco speaking children when asked to answer certain questions in class is not always due to their failure to understand spoken and written spanish that is used in class. their silences are responses taking different meanings in specific situations. the silence of the children can be a way of resisting, a way of hiding, and, sometimes, their voices are silenced.